Triclosan Demonstrates Synergic Effect with Amphotericin B and Fluconazole and Induces Apoptosis-Like Cell Death in Cryptococcus neoformans - Movahed, Elaheh; Tan, Grace Min Yi; Munusamy, Komathy; Yeow, Tee Cian; Tay, Sun Tee; Wong, Won Fen; Looi, Chung Yeng (Frontiers in Microbiology, 2016)
Objectives: Cryptococcus neoformans is an opportunistic fungus that causes fatal meningoencephalitis especially in AIDS patients. There is an increasing need for discovery of new anti-cryptococcal drugs due to emergence of resistance cases in recent years. In this study, we aim to elucidate the antifungal effect of triclosan against C. neoformans. Methods: Minimal inhibitory concentration (MIC) of triclosan in different C. neoformans strains was first examined. The in vitro interactions between triclosan and two standard anti-fungal drugs (amphotericin B and fluconazole) were further evaluated by microdilution checkerboard assay. Mechanism of triclosan fungicidal activity was then investigated by viewing the cell morphology under transmission electron microscope. Results: We reported that triclosan potently inhibited the growth of C. neoformans. A combination of triclosan with amphotericin B or with fluconazole enhanced their fungicidal effects. Triclosan-treated C. neoformans displayed characteristics such as nuclear chromatin condensation, extensive intracellular vacuolation and mitochondrial swelling, indicating that triclosan triggered apoptosis-like cell death. Conclusion: In summary, our report suggests triclosan as an independent drug or synergent for C. neoformans treatment.